PENGARUH STRUKTUR ASET, PROFITABILITAS, GROWTH OPPORTUNITY, KEBIJAKAN DIVIDEN, DAN FIRM SIZE TERHADAP STRUKTUR MODAL (Studi Kasus Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2020) - Margaretha Marini Sinaga; Arthur Simanjuntak; Mitha Christina Ginting; Melanthon Rumapea (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This research aims to determine the influence of asset structure, profitability, growth opportunity, dividend policy, firm size on capital structures in LQ45 companies listed on the Indonesia Stock Exchange in 2015-2020. This study uses secondary data that can be accessed through the Indonesia Stock Exchange website (www.idx.co.id). The population of the study consisted of 45 companies and the sampling method was carried out by purposive sampling method. The results of this study show that asset structure has a significant negative effect on capital structure, profitability has a significant positive effect on capital structure, growth opportunity has no significant negative effect (no effect) on capital structure, dividend policy has no negative effect (no effect) on capital structure, firm size has no negative effect (no effect) on capital structure. asset structure, profitability, growth opportunity, dividend policy, and firm size have a significant effect on the capital structure of LQ45 companies listed on the Stock Exchange (Period 2015-2020).